2017
DOI: 10.1038/s41598-017-14634-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Smoke Impairs Normal Mesenchymal Stem Cell Differentiation

Abstract: Electronic cigarettes (e-cigarettes) are promoted as low-risk alternatives to combustible cigarettes. However, the effects of chronic inhalation of potential toxicants emitted by ecigarettes remain largely unexamined. It is conceivable that smoking-induced chronic diseases result in cellular injury, in the absence of effective repair by stem cells. This study evaluates the effect of cigarette and e-cigarette aerosol extracts on the survival and differentiation of bone marrow-derived mesenchymal stem cells (MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 72 publications
7
37
0
1
Order By: Relevance
“…However, this study did not include CS exposure and thus does not support direct comparison of effect sizes between e-vapor liquid and CS (extracts). Shaito et al demonstrated that CS exposure impairs the in vitro differentiation of mesenchymal stem cells towards the osteoblast linage (Shaito et al 2017). In this study, qualitatively similar effects were observed for the tested e-vapor extracts, but with less pronounced effects.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, this study did not include CS exposure and thus does not support direct comparison of effect sizes between e-vapor liquid and CS (extracts). Shaito et al demonstrated that CS exposure impairs the in vitro differentiation of mesenchymal stem cells towards the osteoblast linage (Shaito et al 2017). In this study, qualitatively similar effects were observed for the tested e-vapor extracts, but with less pronounced effects.…”
Section: Discussionsupporting
confidence: 84%
“…Further investigation is needed to identify the effects of smoking on i.e., collagen structure. Shaito et al (Shaito et al 2017) showed that CS and e-vapor aerosol extracts both caused a reduction in collagen-1 and Runx2 expression as well as alkaline phosphatase activity on mesenchymal stem cell differentiation towards the osteoblast lineage. This could reflect changes in the bone matrix.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a previous study finding no effect of exposure to nicotine on lipid accumulation in beige adipocytes [39].This reduced differentiation potential caused by CS that we observed in our study is consistent with in vitro studies of osteogenic differentiation of mesenchymal stem cells (MSCs) [47,48]. Indeed, Shaito and co-workers showed that both CS and ECIG extracts prevented osteogenic differentiation from progressing [47]. The very low Ucp1 expression in cells not stimulated with forskolin is in line with previous studies [25].…”
Section: Discussionsupporting
confidence: 94%
“…3T3-L1 adipocytes have indeed been shown to express nAChRs and respond to nicotine concentrations within the range that were used herein [10].The inability of pure nicotine to affect markers of differentiation (relative to ambient air extract) indicated that nicotine by itself had no impact at the levels used in these experiments. This is in agreement with a previous study finding no effect of exposure to nicotine on lipid accumulation in beige adipocytes [39].This reduced differentiation potential caused by CS that we observed in our study is consistent with in vitro studies of osteogenic differentiation of mesenchymal stem cells (MSCs) [47,48]. Indeed, Shaito and co-workers showed that both CS and ECIG extracts prevented osteogenic differentiation from progressing [47].…”
Section: Discussionsupporting
confidence: 94%
“…Real time-PCR primers are listed in Table 1. Briefly, extraction of total RNA from cells was performed using RNeasy ® Plus Mini Kit (QIAGEN, Hilden, Germany) while extraction of RNA from mouse or human tissues was performed using TRIzol ® Reagent (Invitrogen), following the manufacturer's protocols and as previously described [95]. One µg of total RNA was reverse-transcribed to a single stranded complementary DNA (cDNA) using Revert Aid first strand cDNA synthesis kit (Thermo, Waltham, MA, USA).…”
Section: Gene Expression Analysis By Quantitative Real-time Polymerasmentioning
confidence: 99%